VD_FINDINFO HC / 2019 / 421 vom 25. April 2019 - VD Tribunal cantonal (2019)
RELATIONS PERSONNELLES, VACANCES, MESURE PROVISIONNELLE | 273 al. 1 CC, 273 al. 1 CPC (CH), 298 CPC (CH), 316 al. 1 CPC (CH)